Do patients return to sports and work after total shoulder replacement surgery?: $hMatthias Bülhoff, Peter Sattler, Thomas Bruckner, Markus Loew, Felix Zeifang, and Patric Raiss - Bülhoff, Matthias; Sattler, Lars Peter; Bruckner, Thomas; Loew, Markus; Zeifang, Felix; Raiss, Patric (The American journal of sports medicine, 2015)
Studies evaluating the return to sports and work after shoulder arthroplasty are rare, and there are no studies evaluating return to work after total shoulder arthroplasty (TSA).